2022
DOI: 10.3390/nano12111814
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behaviors of Cationic Methylene Blue and Anionic Reactive Blue 19 Dyes onto Nano-Carbon Adsorbent Carbonized from Small Precursors

Abstract: In this work, an innovative nano-carbon material (N-CM) adsorbent was reported for exploring its adsorption behaviors toward cationic methylene blue (MB) and anionic reactive blue 19 (RB19) pollutants. The proposed N-CM was synthesized by a one-step solvothermal treatment of citric acid and zinc gluconate small precursors. N-CM consists of nanosheets that have an advantageous specific surface area, large sp2/sp3 hybridized domains, and abundant nitrogen/oxygen-containing surface functional groups. The synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The reason for this result is mainly that the initial MB concentration remained unchanged in the solution. With the increase of EVC-2 dosage, the adsorption active sites on EVC-2 were redundant and could not be fully utilized [ 39 ]. The effect of temperature on MB adsorption capacity at 10, 20, 30, and 40 °C is illustrated in Figure 5 d. The adsorption capacity was enhanced when the temperature rose from 10 to 30 °C, implying it was an endothermic process resulting from the π–π interaction between EVC-2 and MB [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this result is mainly that the initial MB concentration remained unchanged in the solution. With the increase of EVC-2 dosage, the adsorption active sites on EVC-2 were redundant and could not be fully utilized [ 39 ]. The effect of temperature on MB adsorption capacity at 10, 20, 30, and 40 °C is illustrated in Figure 5 d. The adsorption capacity was enhanced when the temperature rose from 10 to 30 °C, implying it was an endothermic process resulting from the π–π interaction between EVC-2 and MB [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, values reported byKumar et al (2020) for some adsorbents used for the removal of methylene blue showed that the adsorption capacities ranged from 0.1883 to 0.3890 while the initial rate ranged from 0.4053 to 1.0519 respectively. Elovich model has also been reportedly obeyed for the adsorption of methylene on silver carbon nanotube and zinc oxide nanoparticles(El-Khatib et al, 2019) Liang et al (2022). also reported 𝛽 = 0.132 𝑔/𝑚𝑔 for the adsorption of MBD by nanocarbon adsorbent and aligned the adsorption kinetics to fit Elovic and pseudo second-order model best.Weber Moris (W-M) intraparticle model (equation13) is appropriate for the description of the extent of involvement of diffusion to the adsorption removal of MBD dye by CaONPO(Oyelude et al, 2017)…”
mentioning
confidence: 86%
“…Table 2 lists the estimated adsorption coefficients. R 2 scores are the main indicators of the precision and caliber of the linear fit procedure [49,50]. The modeling precision is demonstrated by the R 2 values in Table 2, where Langmuir (R 1 2 = 0.9981, 0.9944) > Temkin (R 3 2 = 0.8370, 0.8327) > Freundlich (R 2 2 = 0.8276, 0.8276) for the BCG and BPB dyes, respectively.…”
Section: Adsorption Kineticsmentioning
confidence: 97%
“…The decrease in ∆G • values with temperature shows that higher temperatures favor adsorption. The positive ∆H • values imply the occurrence of endothermic adsorption processes, while the positive ∆S • values indicate random development at the Ag-NP/dye solid-solution interface [49]. Furthermore, the reduction in the ∆G • value of BCG at temperatures ranging from 288 to 298 K demonstrates that its adsorption onto Ag-NPs is promoted by rising temperature.…”
Section: Adsorption Thermodynamicsmentioning
confidence: 99%